Proteinuria in special populations: pregnant women and children - Hladunewich, Michelle A.; Schaefer, Franz (Advances in chronic kidney disease, 2011)
Proteinuria is the hallmark of glomerular kidney disease. It is used diagnostically to follow disease progression and to determine response to therapy. Thus, it is necessary to have an understanding of the mechanisms of proteinuria and the limitations to its accurate assessment in special populations. In this article, we review 2 special populations--pregnant women and children--providing insight into their unique circumstances that require consideration when assessing proteinuria.
Gesehen am 12.09.2022